Selective functionalization of mesoporous UV photonic crystals for the detection of organic vapors - Josefina Morrone; Paula C. Angelomé; Andrés Zelcer; M. Cecilia Fuertes; M. Cecilia Fuertes (Frontiers in Nanotechnology)
Mechanically robust and chemically stable responsive photonic crystals (PC), featuring a photonic band gap centered in the UV region and exhibiting very high reflectivities, were fabricated by alternate deposition of mesoporous zirconia and silica thin films. These multilayered structures were synthesized via dip-coating, using a sol-gel method combined with self-assembly of surfactants, to give rise to the mesoporosity, in which capillary condensation can take place. By exploiting the chemical differences between silicon and zirconium oxides, selective functionalization of the layers that compose the PC was achieved, as demonstrated by infrared spectroscopy, energy dispersive spectroscopy and contact angle measurements. Once obtained, the functionalized PC were tested for vapors detection using water and non-polar organic solvents. The obtained results indicate that water entrance within the PC can be hindered by the presence of organic functions, while organic solvents can be detected in any case. Thus, the selective functionalization strategy developed allows the precise control over the PC response toward analytes with varying physicochemical properties. Moreover, the band gap located in the UV region allows the combination of the developed PC with other sensing devices working in the visible region of the spectrum, paving the way towards the production of highly tunable sensor arrays.